Regulatory and legal provisions and conceptual approaches to optimizing the competences of local government bodies under the conditions of decentralization reform - Vandiak , Anastasia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
This article examines the normative and legal basis for optimizing the capacities of local self-government institutions in the context of modern public administration challenges. It emphasizes the importance of establishing a balanced system of power distribution between state authorities and local self-government institutions in order to increase the efficiency of their activities, ensure transparency and respect the principle of subsidiarity. Modern approaches to optimizing competencies are considered, including the introduction of innovative management practices, digital technologies, and strategic planning for community development. It is noteworthy that effective functioning of local self-government institutions is possible through modernization of legal norms, taking into account national and international practices. The article also analyses the challenges faced by local self-government institutions, including insufficient regulatory provisions for the decentralization process, the lack of clear criteria for the allocation of powers and financial resources, and the difficulties in implementing digital tools. The authors make a number of recommendations for improving the normative and legal framework, including the development of clear criteria for the interaction between authorities at different levels, the promotion of citizen participation, and the introduction of tools to monitor the effectiveness of local self-government institutions. Based on the analysis, the article concludes that the reform of the local self-government system should be based on a comprehensive approach of legal innovation, organizational innovation, technological innovation, etc., with the goal of improving the quality of government, ensuring transparency and adapting to social needs.